Біологічні особливості насіння Securinega suffruticosa (Pall.) Rehd. в умовах Правобережного Лісостепу України - Koldar, L.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
The correlation between seed germination of Securinega suffruticisa (Pall.) Rehd. and harvest dates as well as temperature conditions of its germination was studied. The end of October and beginning of November were found to be optimum harvest dates.